Extending SUSY reach at the CERN large hadron collider using b-tagging - Mercadante, P. G. [UNESP]; Mizukoshi, J. K.; Tata, Xerxes (Sociedade Brasileira de Física, 2007)
We analyze the potential of the CERN Large Hadron Collider on the reach of the focus point (FP) region in the mSUGRA parameter space. This region, consistent with WMAP results, is characterized by multi-TeV masses for the superpartners of quarks and leptons and relatively light charginos and neutralinos. Moreover, since the LSP has a substantial higgsino component, it is expected that the gluino decays predominantly to third generation quarks, producing a final state with multiple hard b jets. Analyzing events with $\not\!\!{E_T}+n$t+ n jets + tagged b-jets, we show that the LHC reach can improve as much as 20% from current projections. Although we performed the analysis specifically for the FP region, the b-tagging should be important to enhance the SUSY signal in a variety of models where a relatively light gluino decays mostly to third generation quarks.
Keywords: SUSY; Supersymmetry; Supergravity; LHC; Jets